(3JMQjQ GdcdGe aj eSGFd GdGdJRGes - (3eMeO Hf eMeO Hf YHO GdQMef GdQYjfqj, CHh YHO Gddg, GdeYQha HGdMWGH,J (B954 (3g` s ((3YeQ Hf eMeO Hf YeQ GdCfOdSj s)
(3ChdgG (B:s
(3GdMeO ddg GdPj YHGOg GdeDefjf GdhaGA HGdYbhO s
(3BNQgG (B:s
(3hQVj Gddg Yf GdJGHYjf hJGHYge HEMSGf Edi jhe GdOjf s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B58 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B230s
Keywords: (3Gdabg GdeGdcjs